2006
DOI: 10.1182/blood-2006-05-024430
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 positively regulates an early step in B-cell development

Abstract: IntroductionB lymphopoiesis involves the expression of multiple factors, including cytokine receptors and transcription factors. [1][2][3] Among the cytokine receptors, Flt3 and IL-7R are known to be critical for early B-cell development. Targeted deletion of Flt3 or Flt3 ligand impairs the development of pro-B and pre-B cells. [4][5][6] Similarly, genetic ablation of the IL-7 or the IL-7R␣ chain results in a developmental block in CLP and pro-B stages. [7][8][9] Mice lacking both Flt3L and IL-7R␣ completely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…It has been shown that Stat3 plays a role in T and B cell development. 24,25 We confirmed that knock-down of Stat3 activity and expression of HIV transgene did not affect T and B cell development in these mice. In a prior study, we found that homozygous Tg26 mice had a small thymus, large spleen, and lymphadenopathy.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It has been shown that Stat3 plays a role in T and B cell development. 24,25 We confirmed that knock-down of Stat3 activity and expression of HIV transgene did not affect T and B cell development in these mice. In a prior study, we found that homozygous Tg26 mice had a small thymus, large spleen, and lymphadenopathy.…”
Section: Discussionsupporting
confidence: 69%
“…BASIC RESEARCH www.jasn.org into the kidney was significantly reduced in Tg26-SA/Ϫ compared with Tg26-SA/ϩ. Because it has been shown that Stat3 plays a role in T and B cell development 24,25 and HIV genes are expressed ubiquitously in Tg26 mice, we sought to determine whether T and B cell development differs between these mice.…”
Section: Resultsmentioning
confidence: 99%
“…Generation and mating of MxCre-STAT3 f/f mice and induction of STAT3 deletion have been described previously (19,20). These animals were maintained and housed in specific germ-free conditions in the Animal Core Facility at the National Taiwan University College of Medicine.…”
Section: Animals and Cellsmentioning
confidence: 99%
“…S1 A and B). Because STAT3 is a major regulator of B-cell development, we examined its activity upon leptin treatment in B cells (18). We found that phosphorylation of STAT3 occurred when leptin was added to spleen B cells in culture, whereas a significantly reduced level of phosphorylated STAT3 was found in db/db mouse B cells (Fig.…”
Section: Resultsmentioning
confidence: 99%